Pengaruh Job Satisfaction Terhadap Tingkat Turnover Intention Pada Guru Di Sekolah X - Siti Nur Salsabila; Rizqi Amalia Aprianty; Dicky Listin Quarta (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Job satisfaction is an important factor that reflects teachers’ comfort, happiness, and positive perception of their work, and is closely related to turnover intention. This study aims to analyze the influence of job satisfaction on turnover intention among teachers at Sekolah X using a quantitative approach. All 37 teachers at X school were selected as participants through total sampling. Data were collected using a job satisfaction scale based on Fattah’s theory (reliability 0.901), which includes five aspects: the work itself, salary, promotion, supervision, and coworkers. Turnover intention was measured using a scale developed from Mobley’s theory (reliability 0.938), covering the aspects of thinking of quitting, intention to search, and intention to quit. The data were then analyzed using simple linear regression with JASP 0.18.3, including normality and linearity tests. The results showed that job satisfaction had a significant and negative effect on turnover intention (R² = 0.402, p < 0.001), indicating that higher job satisfaction corresponds to lower intention to leave. These findings are expected to serve as a basis for developing strategies to improve job satisfaction and reduce turnover intention.